2021
DOI: 10.3390/antiox10121957
|View full text |Cite
|
Sign up to set email alerts
|

l-Arginine Alleviates LPS-Induced Oxidative Stress and Apoptosis via Activating SIRT1-AKT-Nrf2 and SIRT1-FOXO3a Signaling Pathways in C2C12 Myotube Cells

Abstract: l-arginine (l-Arg) has been reported to possess a wide range of functions, including anti-inflammatory, anti-oxidative, and anti-apoptosis. However, the role of l-Arg in LPS-induced muscle injury and its potential protective mechanism has not been well elucidated. This study aimed to investigate the effects of l-Arg on the LPS-induced oxidative stress and apoptosis in differentiated C2C12 myotube cells. Our results demonstrated that myotube cells treated with 0.2 mg/mL LPS significantly decreased cell viabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…Meanwhile, SIRT1/FOXO3a can regulate LPS-induced apoptosis in C2C12 myotube cells. 36 Our study found that TA might induce Ag85B-treated cell apoptosis by regulating SIRT1/FOXO3a signaling. Acetylation and protein levels are usually correlated inversely.…”
Section: Discussionmentioning
confidence: 56%
“…Meanwhile, SIRT1/FOXO3a can regulate LPS-induced apoptosis in C2C12 myotube cells. 36 Our study found that TA might induce Ag85B-treated cell apoptosis by regulating SIRT1/FOXO3a signaling. Acetylation and protein levels are usually correlated inversely.…”
Section: Discussionmentioning
confidence: 56%
“…Although the present and previous studies have found that SIRT1 expression is reduced during inflammatory responses and oxidative damage [ 57 , 66 ], but the underlying mechanism of NMN regulates SIRT1 expression was not well elucidated. In our present study, the expression of SIRT1 and PGC-1α mRNA was also decreased in CLP mice or LPS-stimulated cells, and this change was alleviated by NMN treatment.…”
Section: Discussionmentioning
confidence: 74%
“…AKT1 is the downstream molecule of SIRT1, which has a significant impact on the control of protein synthesis, cell survival and proliferation (Wang et al, 2020). Zhao, et al found that the SIRT1/AKT signaling pathway is involved in the LPS‐induced apoptosis of myotube cells (Zhao et al, 2021). In our validation experiments, expression of SIRT1 and AKT1 was increased in LPS‐induced rats, but was reversed by SJZD.…”
Section: Discussionmentioning
confidence: 99%